2000
DOI: 10.1161/01.atv.20.7.1831
|View full text |Cite
|
Sign up to set email alerts
|

Hyperlipidemia Promotes Thrombosis After Injury to Atherosclerotic Vessels in Apolipoprotein E–Deficient Mice

Abstract: Abstract-The increased risk of hyperlipidemia on the development of complications of atherosclerosis is well established.Cholesterol-lowering therapies lead to a decrease in the incidence of vascular thrombotic events that is out of proportion to the reduction in plaque size. This suggests that the occurrence of acute thrombosis overlying a disrupted plaque is influenced by changes in lipid levels. The influence of acute hyperlipidemia on the development of thrombosis overlying an atherosclerotic plaque in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 29 publications
3
68
0
1
Order By: Relevance
“…Hypercholesterolemia has been shown to influence the arterial thrombotic response after injury [12].…”
Section: Effect Of Ho-1 Gene Transfer On Thrombotic Response To Artermentioning
confidence: 99%
See 1 more Smart Citation
“…Hypercholesterolemia has been shown to influence the arterial thrombotic response after injury [12].…”
Section: Effect Of Ho-1 Gene Transfer On Thrombotic Response To Artermentioning
confidence: 99%
“…It is a complex process influenced by coagulation and fibrinolytic pathways [9,10], inflammation [11], and hypercholesterolemic state [12]. The first line of evidence supporting the anti-thrombotic effect of HO-1 in vivo is the observation that CO suppressed vascular thrombosis occurring during the cardiac graft rejection likely through inhibiting platelet aggregation [13].…”
Section: Introductionmentioning
confidence: 99%
“…One possibility for this refractiveness in the absence of challenge is a possible redundancy of PAI-1 single functions with other proteins. On the other hand, a number of studies have indicated that a deficiency of PAI-1 in mice is manifested by altered responses to vascular and dermal injury (31)(32)(33)(34), tumor growth and angiogenesis (19,(35)(36)(37), and clot lysis (30). As a result, under these challenge conditions, a functional redundancy may be overwhelmed, and the multiplicity of functions in a single protein may offer the most broad and economical response.…”
Section: Lrp-binding Abilities Of Murine Pai-1 Variants-mentioning
confidence: 99%
“…A recent study demonstrated that activation of platelets with a specific oxidized choline glycerophospholipid (oxPC CD36 ) is mediated by CD36 (16). Moreover, hypercholesterolemic mice exhibit a shortened time to occlusion in a carotid artery thrombosis model compared with healthy mice (16)(17)(18)(19). At present, the mechanism underlying the systemic activation of coagulation associated with hypercholesterolemia has not been defined.…”
Section: Introductionmentioning
confidence: 99%